Precision medicine in allergic disease—food allergy, drug allergy, and anaphylaxis—PRACTALL document of the European Academy of Allergy and Clinical Immunology and the American Academy of Allergy, Asthma and Immunology - Muraro, A.; Lemanske, R. F.; Castells, M.; Torres, M. J.; Khan, D.; Simon, H.‐U.; Bindslev‐Jensen, C.; Burks, W.; Poulsen, L. K.; Sampson, H. A.; Worm, M.; Nadeau, K. C. (Allergy (Copenhagen), 2017)
This consensus document summarizes the current knowledge on the potential for precision medicine in food allergy, drug allergy, and anaphylaxis under the auspices of the PRACTALL collaboration platform. PRACTALL is a joint effort of the European Academy of Allergy and Clinical Immunology and the American Academy of Allergy, Asthma and Immunology, which aims to synchronize the European and American approaches to allergy care. Precision medicine is an emerging approach for disease treatment based on disease endotypes, which are phenotypic subclasses associated with specific mechanisms underlying the disease. Although significant progress has been made in defining endotypes for asthma, definitions of endotypes for food and drug allergy or for anaphylaxis lag behind. Progress has been made in discovery of biomarkers to guide a precision medicine approach to treatment of food and drug allergy, but further validation and quantification of these biomarkers are needed to allow their translation into practice in the clinical management of allergic disease.